Chirality and solvent assisted gelation modulation with stearoyl appended macromolecules. (15th August 2022) - Nayak, Kasturee; Sahoo, Subhasish; De, Priyadarsi
Graphical abstract: Abstract: The proper mechanistic understanding of solvent-gelator interaction and gelator-gelator interaction remains mostly unknown leading to a backdrop over the better formulation of polymeric organogelators. Herein, we have designed and synthesized poly(methacrylate) based organogelators having co-tethered fatty acid (stearic acid) and l /d -amino acid (l /d -valine) side chains, and explored their role in thermal-induced gelation in various hydrocarbon solvents, mainly in tetradecane and heptane. Interestingly, we found changes in gelation behaviour with respect to gelator and solvent (going from heptane to tetradecane), as gelation time and minimum gelation concentration (MGC) can be significantly affected by changing solvent and stereoselectivity of the gelators. Mechanical properties and stability of gels have been demonstrated from storage modulus versus angular frequency plot, and rheological temperature sweep experiment from gel-to-sol transition temperature ( T gel ), respectively. Electron microscopy was used to understand the gelation process by understanding the colloidal growth of gelators. The transitions in the structures of the gelators were shown with field emission scanning electron microscopy (FESEM). The variation in gelation behaviour is proposed with different gelation mechanisms; anticipated with dissimilar phase separation mechanisms in different solvents.